A Decade of Knowledge Without Borders: Open Access and Global Reach of School Social Work Research - Leticia Villarreal Sosa (International Journal of School Social Work, 2025)
As we celebrate the 10th anniversary of the International Journal for School Social Work (IJSSW), this article provides a reflection on a decade the last decade of breaking barriers and building bridges across practitioners, researchers, communities, and continents and looks forward to our responsibility for the future. This article discusses the benefits and challenges related to Open Access publishing, and addresses how Open Access is a public good—ensuring that practitioners, researchers, students, and policymakers can engage the best evidence regardless of geography, resources, or institutional affiliation. The impact of IJSSW is reviewed, including a summary of accomplishments, most downloaded and cited articles, and goals for the future. The IJSSW community that has grown around the mission to democratize knowledge—authors, reviewers, editors, school social workers, educators, and students—reminds us that scholarship thrives when it is shared. Open access has helped transform international school social work into a more connected, responsive, and globally informed field.
Keywords: Open Access; Global Social Work; School Social Work